2007
DOI: 10.1093/cercor/bhl183
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Pathophysiology of Auditory/Verbal Hallucinations by Combining Functional Magnetic Resonance Imaging and Transcranial Magnetic Stimulation

Abstract: Functional magnetic resonance imaging and repetitive transcranial magnetic stimulation (rTMS) were used to explore the pathophysiology of auditory/verbal hallucinations (AVHs). Sixteen patients with schizophrenia-spectrum disorder were studied with continuous or near continuous AVHs. For patients with intermittent hallucinations (N = 8), blood oxygenation level-dependent (BOLD) activation maps comparing hallucination and nonhallucination periods were generated. For patients with continuous hallucinations (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 55 publications
7
95
0
4
Order By: Relevance
“…attention regulation, response selection, priority formation, and error monitoring) over incoming stimuli [28]. Activity in Broca’s area, which is normally associated with the motor generation of speech, has also been found in studies of VAHs [29]. The involvement of the right homologue of Broca’s area is consistent with earlier findings in fMRI studies [18,30].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…attention regulation, response selection, priority formation, and error monitoring) over incoming stimuli [28]. Activity in Broca’s area, which is normally associated with the motor generation of speech, has also been found in studies of VAHs [29]. The involvement of the right homologue of Broca’s area is consistent with earlier findings in fMRI studies [18,30].…”
Section: Discussionsupporting
confidence: 76%
“…From previous fMRI analyses examining single subjects and groups of patients experiencing VAHs exclusively, it would seem that concomitant activation of visual and auditory cortices is quite uncommon to the extent shown in this case report [18,29]. According to the subjective reports of patient A, her VAHs were continuously accompanied by changes within the visual field (metamorphopsias), albeit of a varying nature and intensity.…”
Section: Discussionmentioning
confidence: 60%
“…33 A critical role of the temporal cortex in AVH is directly supported by transcranial magnetic stimulation studies, which show that targeting the left temporoparietal region is most effective in reducing AVHs. 34,35 In a follow-up exploratory analysis, we also showed that severity of hallucinations was associated with rGMR in the right superior temporal cortex and cerebellum. These results are consistent with the superior temporal region's putative role in the recognition of prosody and emotional characteristics of perceived speech.…”
Section: Discussionmentioning
confidence: 64%
“…They observed the need for individual assessment of the functional anatomy of hallucinations, using hallucinationactivation maps obtained either by PET or fMRI, and stereotaxically determined the stimulation site following individual fMRI detection of inner speech regions instead of less sophisticated approach including coil position using the international 10/20 EEG electrode system in TP3 site, which might enhance TMS efficacy [43]. A critical finding in a study by Hoffman et al concerned the discrepancy between the fMRI-guided TPC sites used in their trial and the standard TP3 which had little to no overlap [44]. Moreover, in a study by Sommer et al, five of the seven patients undergoing functional guided rTMS had predominant rightsided hallucinatory activity and were therefore stimulated over the right TPC [28,45].…”
Section: Current Results Of Clinical Studies and Meta-analysesmentioning
confidence: 99%